THE ROLE OF DAI IN IMPROVING ADOLESCENT MORALITY IN PALU CITY - Datumula, Sarpika; Khalid, Moh. Yusuf (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2025)
This study concludes that the da'wah activities carried out by HIDMI Palu City are in the form of routine recitation at least once a week by inviting dai/muballig/ustaz. The da'wah material presented focuses on ethics and worship. With da'wah activities as mentioned, it turns out that it has a very positive influence on adolescents in an effort to realize Islamic morality, namely having noble morality to Allah swt and fellow humans. Morality towards Allah can be seen by the perseverance of street children in carrying out worship such as obligatory prayers. Meanwhile, the morality of fellow human beings can be seen from the aspect of the behavior of street children towards their friends, and towards the surrounding community so far. Because da'wah activities have a very urgent and significant role in improving the morality of street children in Palu City, it is hoped that da'wah activities will always be encouraged and managed effectively.